A generalized approach on microwave processing for the lateral and radial irradiations of various Groups of food materials. (February 2016) - Basak, Tanmay; Bhattacharya, Madhuchhanda; Panda, Soumen
Abstract: Numerical studies have been carried out for microwave heating of food samples. It has been shown that the food materials can be divided into four groups based on the values of fp and fw and the microwave heating characteristics remain same for the materials in each group. The heating characteristics of each group of materials have been presented based on the heating front, heating rate and heating nonuniformity (thermal runaway). These characteristics are shown to be strongly dependent on sample size, which can be classified as thin (uniform heating), intermediate (localized heating fronts driven be resonances of microwave power absorption) and thick (exponential attenuation of heating rate from the exposed surface). The analysis shows that the localized heating in intermediate and thick samples can lead to significant thermal runaway, which can be efficiently avoided by selecting radial irradiation over lateral irradiation but at the expense of higher processing time. Highlights: Numerical investigation on microwave heating in various food materials has been carried out. Lateral and radial incidences of TM z polarized microwave are performed for cylindrical samples. Food materials are categorized into four groups based on dimensionless parameters, fp and fw . Variation of average power with sample size is examined for all Groups. Generic pattern of heating fronts is demonstrated for each group of food materials.